Exposure to ultrafine particles and black carbon in diesel-powered commuter trains. (April 2017) - Jeong, Cheol-Heon; Traub, Alison; Evans, Greg J.
Abstract: Ultrafine particle (UFP), black carbon (BC) and lung deposited surface area (LDSA) concentrations measured during 43 trips on diesel-powered commuter trains revealed elevated exposures under some conditions. When the passenger coaches were pulled by a locomotive, the geometric mean concentrations of UFP, LDSA, and BC were 18, 10, and 6 times higher than the exposure levels when the locomotive pushed the coaches, respectively. In addition, UFP, LDSA, and BC concentrations in pull-trains were 5, 3, and 4 times higher than concentrations measured while walking on city sidewalks, respectively. Exposure to these pollutants was most elevated in the coach located closest to the locomotive: geometric means were 126, 000 # cm −3 for UFP, 249 μm 2  cm −3 for LDSA, and 17, 800 ng m −3 of BC; these concentrations are much higher than those previously reported for other modes of public transportation. Markedly high levels of diesel exhaust are present in passenger trains powered by diesel locomotives operated in pull-mode. Thus, it is recommended that immediate steps be taken to evaluate, and where needed, mitigate exposure in diesel-powered passenger trains, both commuter and inter-city. Graphical abstract: Highlights: Ultrafine particles (UFP) and black carbon (BC) were measured in passenger trains. Train passengers can be exposed to elevated levels of diesel exhaust. UFP and BC in pull-trains were notably higher than those for other commuter modes. Mitigating actions for exposure in diesel-powered passenger trains are recommended.